Invasive Pulmonary Aspergillosis Mimicking Cyst Hydatics - Ağababaoğlu, İsmail; Ersöz, Hasan; Çetinkaya Ethemoğlu, Filiz Banu; Şanlı, Aydın (Acta Medica, 2019)
Invasive pulmonary aspergillosis (IPA) is a less frequent form and rarely has been reported in normal immune system cases. They do not constitute radiologically cystic structures. A 53-year-old male who was engaged in stock farming and agriculture has no additional disease or habit in the patient history that would compromise the immune system. In thorax computed tomography, a 11x8x10 cm diaphragmatic invasive cystic lesion was seen in the middle and lower lobes of the right lung, was reported that there may be hydatid cyst. The patient underwent right lower bilobectomy and diaphragm resection, diaphragm was reconstructed with a dual mesh. Histopathologic diagnosis was reported as invasive pulmonary aspergillosis. There was no complication or recurrence in the case in the 24-month follow-up period. Thus, a cure was provided for our patient with invasive pulmonary aspergillosis, which was coincidentally diagnosed by pathology in the postoperative period.